Antiproliferative activity of olomoucine II, a novel 2,6,9-trisubstituted purine cyclin-dependent kinase inhibitor - Krystof, V; McNae, I W; Walkinshaw, M D; Fischer, P M; Müller, P; Vojtesek, B; Orság, M; Havlícek, L; Strnad, M (Cellular and molecular life sciences, 2005)
The study describes the protein kinase selectivity profile, as well as the binding mode of olomoucine II in the catalytic cleft of CDK2, as determined from cocrystal analysis. Apart from the main cell cycle-regulating kinase CDK2, olomoucine II exerts specificity for CDK7 and CDK9, with important functions in the regulation of RNA transcription. In vitro anticancer activity of the inhibitor in a panel of tumor cell lines shows a wide potency range with a slight preference for cells harboring a wild-type p53 gene. Cell-based assays confirmed activation of p53 protein levels and events leading to accumulation of p21(WAF1). Additionally, in olomoucine II-treated cells, Mdm2 was found to form a complex with the ribosomal protein L11, which inhibits Mdm2 ubiquitin ligase function. We conclude that perturbations in RNA synthesis may lead to activation of p53 and that this contributes to the antiproliferative potency of cyclindependent kinase inhibitors.
Keywords: Tumor Suppressor Protein p53; Nuclear Proteins; Growth Inhibitors; kinasy CDC2-CDC28; Cell Line, Tumor; jaderné proteiny; vazebná místa; protoonkogenní proteiny c-mdm2; inhibitory růstu; puriny; Enzyme Inhibitors; Transcription, Genetic; lidé; Antineoplastic Agents; protinádorové látky; ribozomální proteiny; protoonkogenní proteiny; CDC2-CDC28 Kinases; Proto-Oncogene Proteins c-mdm2; genetická transkripce; cyklin-dependentní kinasa 2; inhibitory enzymů; nádorový supresorový protein p53; Proto-Oncogene Proteins; Purines; Ribosomal Proteins; Cyclin-Dependent Kinase 2; nádorové buněčné linie; Binding Sites; Humans